Pelatihan Keselamatan dan Kesehatan Kerja (K3) bagi Siswa SMK Negeri 3 Ogan Komering Ulu dalam Persiapan Praktik Kerja - Safaruddin Safaruddin; Defi Pujianto; Kadarsih Kadarsih (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2026)
Occupational Safety and Health (OSH) is a fundamental competence required by vocational school students before entering workplace practice, particularly due to their high exposure to practical activities involving tools, machines, and work procedures with potential risks. This community service activity aimed to provide OSH training for students of SMK Negeri 3 Ogan Komering Ulu as part of their preparation for workplace practice. The activity was conducted using a seminar and case study approach involving 40 vocational students. The implementation stages included preliminary needs analysis, training delivery through structured material sessions and interactive discussions, and post-training evaluation using participant feedback instruments. The training materials covered formal OSH regulations, basic OSH principles, risk mitigation, personal protective equipment, and the relevance of OSH competencies in industrial work environments. The results indicated that participants demonstrated improved understanding of OSH obligations, awareness of workplace risk prevention, and readiness to apply OSH principles during practical learning activities. This community service activity contributes to strengthening students’ preparedness for workplace practice by fostering early awareness of occupational safety culture within the vocational education context.